Free-living nematodes. Section 3: Enoploidea from subantarctic stations - Mawson, P. M. (B.A.N.Z. Antarctic Research Expedition Reports, Series B, 1958)
Locality: Kerguelen Islands, Macquarie Island; Cabinet:
Locality: Kerguelen Islands, Macquarie Island; Cabinet:; NeMys doc_id: 3821